342. "MEDIRAD – Implications of Medical Low Dose Radiation Exposure": A European-funded project aims to enhance the protection of patients and health professionals from exposure to low dose medical radiation. (December 2018) - Palma, A.; Cisbani, E.; Angelis, C. De; Monaca, S. Della; Dini, V.; Grande, S.; Rosi, A.; ,
Abstract : Purpose: The use of ionising radiation in medicine has been steadily increasing, and this trend is set to continue, with obvious health benefits for the population thanks to improved diagnostic and therapy technologies.However, this increase in radiation exposure levels also raises a number of safety concerns:the potential health effects among patients and medical workers need to be evaluated, dose evaluation tools for clinical practice need to be developed, and practices need to be optimised in order to reduce exposure doses and ensure adequate radiation protection.A new EC-funded project will bring together medical and radiation scientists, physicists and clinicians to enhance the radiation protection of patients and medical professionals.The four-year MEDIRAD project (2017–2021) is led by the European Institute for Biomedical Imaging Research (EIBIR) and comprises a consortium of 33 partners from 14 European countries. Methods: The MEDIRAD Project consists of six interdependent and complimentary work packages (WP), listed in Table. Work Packages Description WP1 : Project management and dissemination Scientific and clinical coordination, ethics management, knowledge management and exploitation, internal and external communication WP2 : Dose evaluation and optimisation in medical imaging Optimisation of chest CT, interventional procedures and multimodality imaging, and development of imaging and radiation dose biobank WP3 : Impact of low dose radiation exposure Standardisation, biokinetic modelling and treatment planning, dosimetry, biomarkers of absorbed doses, protocol for epidemiological study WP4 : Possible health impact of paediatric scanning Epidemiological study on cardiovascular changes after radiotherapy, measuring markers of exposure and risk modelling WP5 : Breast radiotherapy and secondary cardiovascular risk Epidemiological study of paediatric CTs and cancer, including (epi) genetic biomarkers of sensitivity, dosimetry and statistical analyses WP6 : Bringing together medical & nuclear scientific communities Formulation of science-based policy recommendations, consultation of stakeholders, organisation of dissemination seminars Results: MEDIRAD has three major operational objectives:to improve organ dose estimation and registration; to evaluate and understand the mechanisms of the effects of medical exposures, focusing on two outcomes of public health relevance:cardiovascular effects of radiotherapy in breast cancer treatment, and cancer risks following CT scanning in children and adolescents; and to develop science-based consensus policy recommendations for the effective protection of patients, workers and the general public.The ISS, due to its long and consolidated experience in the field of Quality Assurance in Radiological Sciences, has been invited to contribute to the latter issue. Conclusions: MEDIRAD's overall goal is to address these needs by enhancing the scientific bases and practice of radiation protection in medicine. MEDIRAD has received funding from the Euratom research and training programme 2014–2018 (grant agreement N°755523). More information can be found athttp://www.medirad-project.eu/ .